Wound management with negative pressure wound therapy in postoperative infection after open reconstruction of chronic Achilles tendon rupture. (2017) - Saku, Isaku; Kanda, Shotaro; Saito, Toshihiro; Fukushima, Takashi; Akiyama, Toru
Highlights: NPWT can treat postoperative infection following chronic Achilles tendon repair. NPWT is also applicable in cases of tendon loss. NPWT has good functional outcome in postoperative infection for chronic Achilles tendon rupture. Abstract: Introduction: Deep infection after reconstruction of chronic Achilles tendon rupture is a major and intractable complication. Case report: We report a case of late deep infection following a surgery for chronic Achilles tendon rupture, and its simple and successful treatment with negative pressure wound therapy (NPWT). Six months following the reconstruction of chronic Achilles tendon rupture, a deep infection developed and reconstructed part of the tendon ruptured again. After appropriate debridement. Discussion: There is no definitive treatment strategy for postoperative infection following open Achilles tendon repair. NPWT was applied to the wound, to promote wound healing and healthy granulation. In our case, NPWT promoted the wound healing and the infected Achilles tendon with tendon loss formed a healthy bridge with granulation tissue spontaneously. The patient resumed her normal activities of daily living, without requiring tendon transfer surgery. NPWT seems to be a simple and successful candidate for this situation. Conclusion: NPWT seems to be effective for the treatment of postoperative infection following Achilles tendon repair, even in cases of tendon loss.